Isotopic Constraint on the Sources and Biogeochemical Cycling of Nitrate in the Jiulong River Estuary. Issue 3 (15th March 2021) - Wang, Xin; Wu, Xiaoyan; Chen, Min; Cheng, Hua; Chen, Nengwang; Yang, Weifeng; Cai, Yihua
Abstract: Nitrate concentrations and isotopic compositions (δ 15 N‐NO3 − and δ 18 O‐NO3 − ) in the Jiulong River Estuary (JRE) were determined in 2014 to better understand the transformation and source contributions of nitrate. In contrast to nitrate concentrations, which generally followed a conservative binary mixing pattern, both δ 15 N‐NO3 − and δ 18 O‐NO3 − deviated significantly from the binary isotopic mixing lines during all sampling cruises, indicating a dynamic transformation of nitrate in the JRE. The deviation of nitrate isotopic signatures from conservative mixing lines as well as the slope of the regression between N and O isotopes (δ 15 N‐NO3 − vs. δ 18 O‐NO3 − ) had significant seasonal variability, showing the seasonal shifting of the dominant nitrification and sedimentary denitrification in the JRE. Furthermore, the elevated nitrate concentrations and isotopic compositions in the lower JRE during the dry season, along with an isotope regression slope of 1.16, indicated a significant local input of nitrate. Nitrate source apportionment is carried out through the Stable Isotope Analyses in R model with the incorporation of nitrate isotopic fractionation factors for nitrification and denitrification in the JRE. The model results revealed that fertilizer is the largest nitrate source to the JRE, contributing 33%–55% of the nitrate throughout the sampling period. Manure is another major source and contributed 32%–39% of the nitrate to the JRE. Sewage nitrate contributions to the JRE were 7% during April and June but dramatically increased to 18% during the wet season, probably as a result of the rapid flushing of suburban and rural untreated domestic sewage into the river. Plain Language Summary: The Jiulong River Estuary (JRE) has received increasing amounts of riverine nitrate over the last several decades due to the extensive anthropogenic activities in the Jiulong River watershed. However, the sources and biogeochemical cycling of nitrate in the JRE still remain ambiguous. We investigated the nitrate concentrations and isotopic compositions in the JRE in 2014 to better understand the transformation and source contributions of nitrate. Our results suggest a dynamic transformation of nitrate in the JRE and show a seasonal shifting of the dominant nitrification and sedimentary denitrification. Furthermore, the elevated nitrate concentrations and isotopic compositions in the lower JRE, along with an isotope regression slope of 1.16, further indicated a significant local input of nitrate during the dry season. Nitrate source apportionment is carried out through the Stable Isotope Analyses in R model with the incorporation of nitrate isotopic fractionation factors for nitrification and denitrification in the JRE. The model results revealed that fertilizer is the largest nitrate source to the JRE, contributing 33%–55% of the nitrate throughout the sampling period. Manure is another major source and contributed 32%–39% of the nitrate to the JRE. Sewage and rainfall are minor sources to nitrate pools in the JRE. Key Points: The nonconservative mixing behavior of nitrate in the JRE is revealed by nitrate isotopic compositions and concentrations Nitrification and denitrification were dominant N transformation processes as deciphered by nitrate isotopic compositions Fertilizer and manure are major sources of nitrate to the JRE as estimated by SIAR